Sick - Leveen, Tom. (Amulet Books, 2013)
"Brian and his friends are not part of the cool crowd. They're the misfits, the troublemakers--the ones who jump their high school's electrified fence to skip school regularly. So when the virus breaks out, they're the only ones with a chance of surviving"--